Semi-Strong Form Market Efficiency and Resilience of Indonesian Sharia Stocks: An Event Study of the Hamas–Israel Conflict - Ajeng Qurrota A’yun; Windiya Saputri; Anggita Nurcahyani; Nurlatifah Umi Oktafiani; Muhammad Faiz Andeaz Fawwaz (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2026)
This study investigates the market reaction of Indonesian sharia-compliant stocks to the Hamas–Israel conflict announcement on October 7, 2023, through an event study methodology with an event window of [−5, +5] trading days. Using a sample of 35 Indonesia Sharia Stock Index (ISSI) stocks, abnormal returns were analysed via One-Sample t-Tests, Paired Sample t-Tests, and the Wilcoxon Signed Rank Test. Normality tests confirmed non-normal distributions across all event days. Results indicate no significant abnormal returns on ten of eleven event days, supporting semi-strong form market efficiency. However, a statistically significant decline in mean abnormal returns was observed from the pre-event period (mean AR = 0.0325) to the post-event period (mean AR = −0.0611), confirmed by both parametric (t = 2.226, p = 0.033) and non-parametric tests (Z = −2.178, p = 0.029). These findings suggest that Indonesian sharia stocks are relatively resilient to external geopolitical shocks.